NMR based fractal analysis in shale under different confining pressure, and its correlation to Archie's cementation exponents - Zhiqi Zhong; Kaishuo Yang; Qing Yan; Minzhen Li; Lingping Zeng; Lionel Esteban; Yi Wang (Heliyon)
This study delves into the complexity of shale pore structures through fractal dimension analysis of nuclear magnetic resonance (NMR) data under varying confining pressures. Focusing on nine illite-rich shale samples, we investigate how confining pressure influences the pore size distribution, particularly narrowing meso- and macropores. Our analysis utilizes two distinct models to calculate fractal dimensions: Model 1 categorizes pores into micro and meso + macro based on T2 cutoffs, while Model 2 considers all pore sizes collectively. Results show that fractal dimensions increase with confining pressure, indicating enhanced pore complexity. Notably, Model 2 proves more adept for shales, revealing no significant correlation with quartz or total clay content or NMR porosity. However, a robust correlation (R2 = 0.9416) between fractal dimension and Archie's cementation exponent m suggests a novel method for estimating Archie's m through pore distribution analysis without electrical resistivity evaluation. This approach offers new insights for petroleum exploration and pore structure characterization in shales, particularly within the Goldwyer Formation and similar geological settings.